Functional and cognitive aspects of employability: Implications for international students - Bennett, Dawn; Ferns, S. (Springer, 2017)
This chapter reports from a study that examined the work integrated learning experiences of international students studying occupational therapy. We begin by setting the context with a short discussion of higher education, employability and work integrated learning. We then report on three student cases, discussing the students’ development before, during and after their internships. This leads to discussion of a possible model and recommendations for further research.